Integrin-dependent Control of Translation: Engagement of Integrin α(IIb)β(3) Regulates Synthesis of Proteins in Activated Human Platelets - Pabla, Ravinder (The Rockefeller University Press, 1999)
Integrins are widely expressed plasma membrane adhesion molecules that tether cells to matrix proteins and to one another in cell–cell interactions. Integrins also transmit outside-in signals that regulate functional responses of cells, and are known to influence gene expression by regulating transcription. In previous studies we found that platelets, which are naturally occurring anucleate cytoplasts, translate preformed mRNA transcripts when they are activated by outside-in signals. Using strategies that interrupt engagement of integrin α(IIb)β(3) by fibrinogen and platelets deficient in this integrin, we found that α(IIb)β(3) regulates the synthesis of B cell lymphoma 3 (Bcl-3) when platelet aggregation is induced by thrombin. We also found that synthesis of Bcl-3, which occurs via a specialized translation control pathway regulated by mammalian target of rapamycin (mTOR), is induced when platelets adhere to immobilized fibrinogen in the absence of thrombin and when integrin α(IIb)β(3) is engaged by a conformation-altering antibody against integrin α(IIb)β(3). Thus, outside-in signals delivered by integrin α(IIb)β(3) are required for translation of Bcl-3 in thrombin-stimulated aggregated platelets and are sufficient to induce translation of this marker protein in the absence of thrombin. Engagement of integrin α(2)β(1) by collagen also triggered synthesis of Bcl-3. Thus, control of translation may be a general mechanism by which surface adhesion molecules regulate gene expression.